2021
DOI: 10.1016/j.ccell.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous targeting of TGF-β/PD-L1 synergizes with radiotherapy by reprogramming the tumor microenvironment to overcome immune evasion

Abstract: Highlights d BA synergizes with RT to overcome tumor immune evasion via TME reprogramming d Reconstitution of tumor immunosurveillance by BART induces abscopal effects d In fibrotic lungs, PD-L1 + endothelial cells and M2-like lipofibroblasts express TGF-b d BA attenuates lung fibrosis by neutralizing TGF-b in the relevant PD-L1 + compartments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 48 publications
1
69
0
Order By: Relevance
“…The TME provides strong support for tumor cells and has been demonstrated to play pivotal roles in tumor occurrence, progression, metastasis, and the e cacy of therapeutic interventions. [31,32,33] Among the cell types in the TME, immune cells such as macrophages, natural killer cells, neutrophils, dendritic cells, and myeloid derived suppressor cells, play signi cant roles in tumor progression. [34,35,36,37,38,39,40,41,42] In this study,…”
Section: Discussionmentioning
confidence: 99%
“…The TME provides strong support for tumor cells and has been demonstrated to play pivotal roles in tumor occurrence, progression, metastasis, and the e cacy of therapeutic interventions. [31,32,33] Among the cell types in the TME, immune cells such as macrophages, natural killer cells, neutrophils, dendritic cells, and myeloid derived suppressor cells, play signi cant roles in tumor progression. [34,35,36,37,38,39,40,41,42] In this study,…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Lan et al reported the development of bintrafusp alfa, a bifunctional fusion protein composed of the extracellular domain of the TGFβ RII receptor to trap TGFβ, fused to a human immunoglobulin G1 antibody blocking PD-L1 [52]. Using this molecule in combination with RT in several immune-cold murine tumor models, they showed a synergic action leading to higher survival, increased TIL, reprogramming of the TME, and reduced tissue fibrosis [53]. Additionally, regression of spontaneous lung metastases was observed.…”
Section: Combination With Other Therapies 231 Targeting Molecular Modulators Of the Immune Responsementioning
confidence: 99%
“…
In the current issue of Cancer Cell, Lan et al 1 demonstrate that a bifunctional fusion protein targeting TGF-b and PD-L1 can synergize with radiation therapy to simultaneously augment tumor control and reduce normal tissue toxicity.
DECLARATION OF INTERESTSS.F.B. owns equity in, receives compensation from, serves as a consultant for, and sits on the scientific advisory board and board of directors of Volastra Therapeutics, Inc. C.M.R.
…”
mentioning
confidence: 99%
“…In the current issue of Cancer Cell, Lan et al 1 demonstrate that a bifunctional fusion protein targeting TGF-b and PD-L1 can synergize with radiation therapy to simultaneously augment tumor control and reduce normal tissue toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation